Green, Hydrothermal Synthesis of Fluorescent Carbon Nanodots from Gardenia, Enabling the Detection of Metronidazole in Pharmaceuticals and Rabbit Plasma - Yang, Xiupei (Sensors (Basel), 2018)
Strong fluorescent carbon nanodots (FCNs) were synthesized with a green approach using gardenia as a carbon source through a one-step hydrothermal method. FCNs were characterized by their UV-vis absorption spectra, photoluminescence (PL), Fourier transform infrared spectroscopy (FTIR) as well as X-ray photoelectron spectroscopy (XPS). We further explored the use of as-synthesized FCNs as an effective probe for the detection of metronidazole (MNZ), which is based on MNZ-induced fluorescence quenching of FCNs. The proposed method displayed a wide linear range from 0.8 to 225.0 µM with a correlation coefficient of 0.9992 and a limit of detection as low as 279 nM. It was successfully applied to the determination of MNZ in commercial tablets and rabbit plasma with excellent sensitivity and selectivity, which indicates its potential applications in clinical analysis and biologically related studies.